Faktor-Faktor Penentu yang Mempengaruhi Tata Kelola: Tinjauan Literatur Sistematis dan Sintesis untuk Penelitian di Masa Depan - Muslikun Mashadi; Theresia Trisanti; Wisnu Prajogo (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
Effective governance is crucial for accountability, transparency, and efficiency within the public sector. Originating from corporate governance principles like accountability and transparency, it expanded to the public sector, exemplified by frameworks such as the UNDP's good governance initiative. Its implementation faces diverse challenges globally, including corruption in emerging nations and bureaucratic efficiency in affluent ones, highlighting the need for a comprehensive analysis of its determinants. This study aims to uncover the determinants influencing governance and their effects on public accountability, operational efficiency, and social welfare. This research employs a Systematic Literature Review (SLR) methodology following PRISMA principles. A Scopus database search using keywords